Sustainable Communication Practices in Management Control - Are Body and Mind in Conflict or Convertion? - Nørreklit, Hanne; de Witt, Camilla Kølsen (HERMES - Journal of Language and Communication in Business, 2001)
For the manager of a firm to gain success, good ideas and management control systems are probably important, but not sufficient, elements. The manager also needs to be able to communicate his/her ideas and plans convincingly to the employees as they have to execute them. In a decentralised organisation, the need for such effective management is of vital importance. The basic assumption made in this paper is that the successfull manager uses convincing rhetoric which is based on his social competence and his ability to communicate. This assumption is examined by analysing the communication and interaction of a successful division manager who controls 45 rather decentralised profit centres, each of which is headed by a general manager. The rhetorical instruments used by the division manager are studied in order to shed light on his management philosophy, which strongly resembles the philosophy involved in Socratic conversations. The rhetorical analysis provides the background for a preliminary conclusion in this respect: practical division control may gain from being visualised.